Factors Influencing Satisfaction among Employees in Maternity Hospitals - Batbold Tseleejav; Tumurbaatar Luvsansambuu; Erkhembaatar Tudevdorj; Munkhkhand Jurmeddorj; Munkhtsetseg Nyam-Osor; Munkh-Erdene Luvsan (Central Asian Journal of Medical Sciences, 2021)
Objective: To evaluate the level of job satisfaction among the employees of maternity hospitals and to describe variables related to their job satisfaction. Methods: A cross-sectional study was undertaken that focused on 480 full time staff of three maternity hospitals located in the capital city of Mongolia, Ulaanbaatar. Data was collected between July 2019 and September 2019. We selected 3 hospitals as our sample target in order to assess an organizational management capability index using 9 chapters with 90 criteria that used over 30 local public organizations. The Minnesota Satisfaction Questionnaire was used as a data gathering tool to assess employee’s satisfaction which measures on a five-point Likert scale. Results: Overall, 48.0 % of participants had low levels of satisfaction with their jobs. Factors that were statistically significant to employees’ job satisfaction in the univariate analysis were entered into the logistic regression analysis including employees’ professional title, department work hours, work requirements, and life and work stress. The results of the logistic regression analysis suggested that employees’ job satisfaction was related to their age, working hours, leadership attention, wage and promotion as well as cooperation with colleagues. Conclusion: There is an urgent need for maternal hospitals in Mongolia to establish a more reasonable promotion and management system for employees and pay more attention to less-experienced staff and help them release their work stress.